Surface Integrity and Corrosion Resistance of 42CrMo4 High-Strength Steel Strengthened by Hard Turning - Qingzhong Xu (MDPI AG, 2021)
To improve the surface corrosion resistance of 42CrMo4 high-strength steel used in a marine environment, this article studied the effects of hard turning on the surface integrity and corrosion resistance of 42CrMo4 high-strength steel through the single factor experimental method, namely hard turning, polarization corrosion, electrochemical impedance spectroscopy, potentiodynamic polarization curve, and salt spray tests. The results indicated that the surface integrity was modified by the hard turning, with a surface roughness lower than Ra 0.8 μm, decreased surface microhardness, fine and uniform surface microstructure, and dominant surface residual compressive stress. The hard turning process was feasible to strengthen the surface corrosion resistance of 42CrMo4 high-strength steel. The better corrosion resistance of the surface layer than that of the substrate material can be ascribed to the uniform carbides and compact microstructure. The corrosion resistance varied with cutting speeds as a result of the changed surface microhardness and residual compressive stress, varied with feed rates as a result of the changed surface roughness, and varied with cutting depths as a result of the changed surface residual compressive stress, respectively. The surface integrity with smaller surface roughness and microhardness and bigger surface residual compressive stress was beneficial for corrosion resistance.